2019
DOI: 10.1037/ocp0000116
|View full text |Cite
|
Sign up to set email alerts
|

Workplace incivility and employee sleep: The role of rumination and recovery experiences.

Abstract: This study examines the role of negative work rumination and recovery experiences in explaining the association between workplace incivility and employee insomnia symptoms. Drawing on the perseverative cognition model of stress and the effort-recovery model, we hypothesize a moderated mediation model in which workplace incivility is associated with insomnia symptoms via negative work rumination. This indirect effect is proposed to be conditional on employees' reported level of recovery experiences (i.e., psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
121
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(149 citation statements)
references
References 92 publications
13
121
0
2
Order By: Relevance
“…When employees experience depletion of these resources, their ability to accomplish family responsibilities might be impaired. For example, given the ambiguous nature of workplace incivility, targets of workplace incivility are likely to devote additional time and cognitive resources to process their experiences even after work time (Demsky, Fritz, Hammer, & Black, ), thus leaving them less time and fewer cognitive resources to cope with family demands. Further, because targets of workplace incivility are more likely to think about work‐related experiences after the events (Demsky et al, ; Nicholson & Griffin, ), they will be less likely to engage in resource gaining activities such as recovery activities, and thus, their resources can be further depleted even after they are away from work, making them less capable of coping with potential demands from family.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…When employees experience depletion of these resources, their ability to accomplish family responsibilities might be impaired. For example, given the ambiguous nature of workplace incivility, targets of workplace incivility are likely to devote additional time and cognitive resources to process their experiences even after work time (Demsky, Fritz, Hammer, & Black, ), thus leaving them less time and fewer cognitive resources to cope with family demands. Further, because targets of workplace incivility are more likely to think about work‐related experiences after the events (Demsky et al, ; Nicholson & Griffin, ), they will be less likely to engage in resource gaining activities such as recovery activities, and thus, their resources can be further depleted even after they are away from work, making them less capable of coping with potential demands from family.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…For example, given the ambiguous nature of workplace incivility, targets of workplace incivility are likely to devote additional time and cognitive resources to process their experiences even after work time (Demsky, Fritz, Hammer, & Black, ), thus leaving them less time and fewer cognitive resources to cope with family demands. Further, because targets of workplace incivility are more likely to think about work‐related experiences after the events (Demsky et al, ; Nicholson & Griffin, ), they will be less likely to engage in resource gaining activities such as recovery activities, and thus, their resources can be further depleted even after they are away from work, making them less capable of coping with potential demands from family. Furthermore, individuals who experience workplace incivility are likely to experience negative emotions before leaving work due to depleted resources, and this negative effect can spill over to their time after work without sufficient resource recovery (Tremmel & Sonnentag, ; Zhou, Yan, Che, & Meier, ).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study aiming at investigating the relationship between work-related rumination, sleep quality, and work-related fatigue, the three factors structure of the instrument was supported (Querstret & Cropley, 2012). Moreover, affective rumination factor was confirmed via a study investigating the impacts of work-related rumination and recovery on sleep and workplace incivility (Demsky, Fritz, Hammer & Black, 2018). While workrelated rumination questionnaire was widely utilized in English, it was translated into other languages.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, incivility could be considered a threat to the worker's health and personal and social well‐being, since it would reflect the potential loss of a positive and friendly work context. For example, research has shown that when workers are facing situations of incivility, their emotional, energy and cognitive resources can be compromised and translated into a loss of well‐being and health (Demsky, Fritz, Hammer & Black, ; Hershcovis, Cameron, Gervais & Bozeman, ; Taylor et al ., ; Zhou et al ., ).…”
Section: Introductionmentioning
confidence: 99%